2017
DOI: 10.1007/978-3-319-69548-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Ontology for Representing Human Needs

Abstract: Need satisfaction plays a fundamental role in human wellbeing. Hence understanding citizens' needs is crucial for developing a successful social and economic policy. This notwithstanding, the concept of need has not yet found its place in information systems and online tools. Furthermore, assessing needs itself remains a labor-intensive, mostly offline activity, where only a limited support by computational tools is available. In this paper, we make the first step towards employing need management in the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The study of human needs has roots in psychology, economics, philosophy, sociology, anthropology, and social sciences, which indicates the importance of needs, and their satisfaction in human life. Despite that fact, there is still a shortage of incorporating human needs in information systems and tools [14]. Augmented reality is a growing field that may benefit from the utilization of human needs.…”
Section: Problem Definition and Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of human needs has roots in psychology, economics, philosophy, sociology, anthropology, and social sciences, which indicates the importance of needs, and their satisfaction in human life. Despite that fact, there is still a shortage of incorporating human needs in information systems and tools [14]. Augmented reality is a growing field that may benefit from the utilization of human needs.…”
Section: Problem Definition and Motivationmentioning
confidence: 99%
“…Based on the above reasoning, this paper looks into the development of an ontology that combines the concepts of augmented reality, human needs' satisfaction, and the detection of those needs from context and user information to support conceptual modeling. Previous studies on ontologies included a representation of needs as they are found in various theories of human needs [14], an ontology focusing only on Max-Neef's model of human needs [22], context modeling [23], and developing augmented reality based on ontological context awareness [16].…”
Section: Problem Definition and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, POLYPHONY supports disagreement annotations of varying granularity: from the ontology level to the level of single triple, or a collection of triples. As a proof of concept, POLYPHONY was applied to OPENEED, a modular ontology for human needs data proposed by Human et al (2017), to represent disagreements between different modules of the OPENEED ontology, i.e. to annotate epistemic disagreements between needs theories.…”
Section: Conceptualizing Epistemic Disagreements As Digital Artifactsmentioning
confidence: 99%